Scientific Production on Rennet Cheese: Bibliometric Study, Impact, and Trends in the Web of Science Database: Rennet cheese: bibliometric study - Ribeiro, Neila Lidiany; Paixão, Gean Carlos Targino; Almeida, Katcilanya Menezes de; Andrade, Romário Oliveira de; Cordão , Maíza Araújo; Silva, Júlio César Bezerra Vilar da; Negreiros, Natalia Ferreira; Santos, Edilayane da Nóbrega; Ribeiro , Radmila Raianni Alves; Lira, Myrella Cariry; Gurjão, Thyago Araújo; Figueiredo, Caio Franklin Vieira de (Food Science and Technology, 2025)
The objective was to analyze, through a bibliometric review, the evolution of scientific production on coalho cheese, with an emphasis on studies involving goat’s milk, as well as its functional and probiotic properties, highlighting research trends, key authors, institutions, and countries active in the field. The chosen database was Web of Science, due to its high relevance in the academic field. The research was conducted during the first week of June 2025, using the terms "coalho cheese" or "rennet cheese" as a topic filter, searching within titles, abstracts, and keywords. The search resulted in a total of 176 documents related to the investigated topic. Of these, the majority consists of articles, totaling 164. Additionally, seven review articles were found, along with one meeting abstract, one note, and five documents classified as procedural papers. The sum of these classifications exceeds the 176 returned documents, which can be explained by the fact that the database assigned multiple classifications to some of them. The predominant language found is English, with 149 documents, followed by Portuguese with 21. There are also two documents in Russian and two in Spanish, as well as one in German and one in Polish. Based on data analysis, research on coalho cheese has expanded significantly in recent decades, with a substantial increase in the number of publications and citations. Brazil stands out as the main research center for this product, reflecting its cultural, economic, and scientific relevance in the country.